Heme Oxygenases1 (Hmox1) and Serum Ferritin Level between Preeclampsia and Normal Pregnancy - Ridwan A Putra; Jusuf S Effendi; Udin Sabarudin (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To determine the comparison of Hmox-1 to serum ferritin level between patients with preeclampsia and normal pregnancy. Methods: This study used analytic observational with cross sectional design. We included 30 subjects with preeclampsia and the other 30 people with normal pregnancy in accordance with inclusion and exclusion criteria. Examination of Hmox-1 and ferritin level was performed through ELISA method. The data consisted of physical and laboratory examination and they would be continued to the calculation in the statistical analysis. Results: The average of Hmox-1 level in normal pregnancy and preeclampsia was 1.2 (SD 1.6) ng/ml and 0.3 (SD 0.2) ng/ml (p